2020
DOI: 10.1177/1120672120931025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and grading of Kayser–Fleischer ring in Wilson disease by Scheimpflug camera

Abstract: Purpose: Evaluation the anterior segment parameters of Wilson disease patients with Kayser–Fleischer ring, the diagnostic power of Scheimpflug imaging for Kayser–Fleischer ring and suggest a scoring system. Materials and Methods: A total of 44 eyes of 22 Wilson disease patients with Kayser–Fleischer ring and 40 right eyes of 40 healthy age matched subjects were enrolled to the study. Serum ceruloplasmin and urine copper/24 hours levels were recorded. Anterior segment parameters including steep and flat keratom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Moreover, it was found that the WD-N group had a higher incidence of the K-F ring than the no-WD-N group. These results are consistent with previous research findings (16,(32)(33)(34). Furthermore, the WD-N group had significantly higher psychiatric symptom scores and liver symptom scores than the no-WD-N group.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, it was found that the WD-N group had a higher incidence of the K-F ring than the no-WD-N group. These results are consistent with previous research findings (16,(32)(33)(34). Furthermore, the WD-N group had significantly higher psychiatric symptom scores and liver symptom scores than the no-WD-N group.…”
Section: Discussionsupporting
confidence: 93%
“…[ 34 ] and Degirmenci, C, etc. [ 11 ], including the scope and Scheimpflug imaging. In this research, K–F ring were graded in five grades, of which is grade 0 to 4.…”
Section: Methodsmentioning
confidence: 99%
“…The corneal K–F (Kayser Fleischer) ring is the most common ophthalmic manifestation of WD patients. K–F ring usually exists in 90.4%–100% of WD patients with neuropsychiatric symptoms, and 50–60% of WD patients without neurological symptoms, but only in 10%–40% of asymptomatic WD patients [ [10] , [11] , [12] , [13] ]. The K–F ring is named after Kayser (1902) and Fleischer (1903) respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Follow-up and multiple examinations of 12 patients of the same cohort suggested that this method may be used to follow-up the patients as a marker of whole-body copper reduction under treatment. In a recent study by Degirmenci and Palamar, Scheimpflug image was used to diagnose and make a grading of KFR in 22 WD patients compared to controls [38]. KFR was observed at the periphery of the cornea as a hyper-reflective area, the extent of which was concordant with KFR severity on SLE.…”
Section: Cornea Involvementmentioning
confidence: 99%